Generation of Drosophila attP containing cell lines using CRISPR-Cas9. Issue 8 (8th May 2021) - Mariyappa, Daniel; Luhur, Arthur; Overton, Danielle; Zelhof, Andrew C
Abstract: The generation of Drosophila stable cell lines has become invaluable for complementing in vivo experiments and as tools for genetic screens. Recent advances utilizing attP/PhiC31 integrase system has permitted the creation of Drosophila cells in which recombination mediated cassette exchange (RMCE) can be utilized to generate stably integrated transgenic cell lines that contain a single copy of the transgene at the desired locus. Current techniques, besides being laborious and introducing extraneous elements, are limited to a handful of cell lines of embryonic origin. Nonetheless, with well over 100 Drosophila cell lines available, including an ever-increasing number CRISPR/Cas9 modified cell lines, a more universal methodology is needed to generate a stably integrated transgenic line from any one of the available Drosophila melanogaster cell lines. Here, we describe a toolkit and procedure that combines CRISPR/Cas9 and theaaa PhiC31 integrase system. We have generated and isolated single cell clones containing an Actin5C::dsRed cassette flanked by attP sites into the genome of Kc167 and S2R+ cell lines that mimic the in vivo attP sites located at 25C6 and 99F8 of the Drosophila genome. Furthermore, we tested the functionality of the attP docking sites utilizing two independent GFP expressing constructs flanked by attB sites that permit RMCE and therefore the insertion of any DNA of interest. Lastly, to demonstrate the universality of our methodology and existing constructs, we have successfully integrated the Actin5C::dsRed cassette flanked by attP sites into two different CNS cell lines, ML-DmBG2-c2 and ML-DmBG3-c2. Overall, the reagents and methodology reported here permit the efficient generation of stable transgenic cassettes with minimal change in the cellular genomes in existing D. melanogaster cell lines.